2021
DOI: 10.3389/falgy.2021.761388
|View full text |Cite|
|
Sign up to set email alerts
|

Patients Unmet Needs in Chronic Rhinosinusitis With Nasal Polyps Care: A Patient Advisory Board Statement of EUFOREA

Abstract: Background: European patients with chronic rhinosinusitis with nasal polyps (CRSwNP) have had only limited occasions to unite to have their voices heard, hence missing the opportunity to contribute to the improvement of CRSwNP care.Aims: To identify unmet needs in CRSwNP from the perspective of CRSwNP patients from the Patient Advisory Board (PAB) of the European Forum for Research and Education in Allergy and Airways diseases (EUFOREA).Methodology: Semi-structured interviews were conducted individually with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 29 publications
3
20
1
Order By: Relevance
“…Participants agreed on the lack of coordination amongst health care contacts, supporting the results of our previous Unmet Needs in CRSwNP initiative by the EUFOREA Patient Advisory Board ( 17 ). Disagreements between physicians, health care inequalities, lack of follow-up, overlooking of comorbidities with focus on one organ, and long waiting lists on the clinics covering the co-morbidities, raised questions about the efficiency and organization of current health care services in different European countries.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Participants agreed on the lack of coordination amongst health care contacts, supporting the results of our previous Unmet Needs in CRSwNP initiative by the EUFOREA Patient Advisory Board ( 17 ). Disagreements between physicians, health care inequalities, lack of follow-up, overlooking of comorbidities with focus on one organ, and long waiting lists on the clinics covering the co-morbidities, raised questions about the efficiency and organization of current health care services in different European countries.…”
Section: Discussionsupporting
confidence: 69%
“…Clear guidelines on the management of asthma, CRSwNP and atopic dermatitis exist but data have shown that few patients are being treated in line with these guidelines ( 28 , 31 ). EUFOREA aims to bridge this gap between guidelines and daily practice ( 17 ). Physicians are required to receive continuous and high-quality education with the aim of having adequate knowledge of the novel treatment options and optimizing timely diagnosis and referral ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with more severe asthma, it has been shown that CRSwNP is more difficult to manage, and that the condition increased the probability of a recurring ESS 30 . However, ESS in CRSwNP patients is associated with a high rate of recurrence which is likely to contribute to the burden of the disease, further exacerbated by comorbidities such as asthma 35,38 …”
Section: Discussionmentioning
confidence: 99%
“…33 Although sinus surgery is an important treatment option for patients with CRSwNP, undergoing repeat surgeries with occasionally only temporary or unpredictable outcomes and potentially long recovery times Fokkens et al is a concern for patients. 35 Repeat surgeries are also associated with increased overall clinical burden (including healthcare resource utilisation and costs). 36 It was therefore important to perform a further in-depth assessment of the effect of mepolizumab on sinus surgery endpoints.…”
Section: Discussionmentioning
confidence: 99%